The Influence of Power Distance on Communication Apprehension among Workers in Palembang City - Siagian, Ade Indriani; Dewi, Evie Ariadne Shinta; Yustikasari, Yustikasari (SEIKO : Journal of Management & Business, 2023)
This research aims to determine the influence of power distance on communication apprehension among workers in Palembang City. The study is based on the Theory of Independent Mindedness. The research design is quantitative, utilizing a questionnaire as the research instrument. The respondents consisted of 100 workers in Palembang. The results of the study indicate a significant influence of power distance on communication apprehension. The findings provide support for the cultural congruence between societal culture (macro) and organizational culture (micro). The results also show a positive influence, meaning that as power distance increases, communication apprehension also increases.